Heap leaching treatment method for argillaceous low-grade uranium-containing molybdenum ore
Through the crushing, maturation and roasting processes, the mineral structure of low-grade uranium-containing molybdenum ore is optimized, combined with acid leaching treatment, the problem of fine and easy mudification of molybdenum mineral embedded cloth is solved, and high-efficiency leaching and low-cost under high piles are achieved. Uranium molybdenum recycling.
Patent Information
- Application Number
- CN202411438236.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
The molybdenum mineral embedded in low-grade uranium-containing molybdenum ore is fine and easy to mudify, making it difficult to achieve efficient leaching under high piles, and the existing technology costs are relatively high.
Optimize the mineral structure through crushing, maturation and roasting processes, and combine acid leaching treatment to improve the leaching performance and permeability of the minerals, and achieve efficient leaching under high piles.
The leaching rate of uranium and molybdenum is significantly improved, the treatment cost is reduced, and excellent leaching effect can be achieved under high heaping conditions and good permeability is maintained.
Smart Images

Figure CN119287179A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrometallurgy, and in particular relates to a heap leaching process for muddy low-grade uranium-containing molybdenum ore. Background Art
[0002] Molybdenum is a rare, refractory metal. Due to its unique atomic structure, it possesses not only excellent mechanical properties such as high-temperature strength, high-temperature hardness, high rigidity, and wear resistance, but also exceptional physical and chemical properties such as good thermal and electrical conductivity, a low coefficient of thermal expansion, and strong corrosion resistance. Therefore, molybdenum and its compounds are widely used in the steel industry, nonferrous metallurgy, chemical industry, agriculture, and other fields. my country has abundant molybdenum reserves, but the types of molybdenum deposits are complex. Molybdenum reserves derived from single ores account for only 29.7% of the country's total reserves, while the remainder are paragenetic deposits such as copper-molybdenum, molybdenum-tungsten, and molybdenum-iron. Because my country's molybdenum deposits are primarily low-grade and difficult to process, comprehensive recovery and utilization of low-grade molybdenum resources is needed.
[0003] A low-grade uranium-containing molybdenum ore deposit in Hebei Province is located. The host rock is volcaniclastic, with complex mineralogy, high oxidation levels, and abundant mud content. The target minerals are extremely finely embedded, predominantly in colloidal form. No crystalline molybdenum minerals are observed under the microscope, and floatability is very poor. The main minerals are limonite, pyrite, molybdenite, and urano-molybdenite. Gangue minerals are primarily quartz, clay minerals, and feldspar. Molybdenum is primarily present in the limonite as molybdenum oxide, with some occurring as molybdenite, urano-molybdenite, blue molybdenite, and colloidal sulfide molybdenite, making it difficult to concentrate and concentrate. Improving the recovery rate of uranium and molybdenum from this type of ore and reducing production costs have long been hot research topics for Chinese researchers.
[0004] Chinese patent publication CN114350985A discloses a method for recovering uranium and molybdenum from encapsulated low-grade uranium-containing molybdenum ore. The invention utilizes a grinding and pressure acid leaching process. The low-grade uranium-containing molybdenum ore is first ground to a particle size of -60 to -200 mesh. The resulting uranium-molybdenum ore is then subjected to pressurized acidic oxidative leaching. The liquid-to-solid ratio of the leaching agent to the uranium-molybdenum ore is 1:1 to 3:1. Sulfuric acid is added to control the initial acidity to 20 to 40 g / L. The reaction is carried out at a total pressure of 0.7 to 0.9 MPa, an oxygen partial pressure of 0.2 to 0.4 MPa, a temperature of 150 to 170°C, and a reaction time of 1 to 4 hours. After the reaction is complete, the slurry is separated into a solid-liquid phase. This method achieves a total uranium recovery rate of 68.2% and a total molybdenum recovery rate of 77.1%. While this method improves molybdenum recovery, the grinding, high-pressure leaching, and solid-liquid separation required for low-grade uranium-containing molybdenum ore incur high production costs.
[0005] Chinese patent publication CN115125405A discloses a method for processing complex, low-grade uranium-containing molybdenum ores. The invention involves crushing the ore, adding a binder, and then acid-granulating it. The ore is then matured at 90-100°C before heap leaching. The uranium leaching rate is 63.4% and the molybdenum leaching rate is 75.0%. This method requires the addition of a binder to ensure heap permeability during heap leaching, requiring a large amount of binder and resulting in high costs. Furthermore, the method does not address the impact of varying heap height on heap permeability.
[0006] Chinese patent publication CNCN115852140A discloses a comprehensive extraction method for complex uranium-molybdenum ores. This method involves crushing the complex uranium-molybdenum ore, mixing it with an oxidant, an activator, and water, and then ball-milling it. The milled material is then slurried and heated and stirred for leaching, followed by solid-liquid separation. The method achieves molybdenum and uranium recovery rates of 79.2% and 66.6%, respectively. This method requires the addition of a large number of reagents during the grinding process, requiring a wide variety of reagents and large quantities, making the system complex and costly. Summary of the Invention
[0007] In view of the problems of the prior art, the object of the present invention is to provide a heap leaching process for muddy low-grade uranium-containing molybdenum ore, aiming to improve the heap leaching effect of muddy low-grade uranium-containing molybdenum ore.
[0008] A heap leaching process for muddy, low-grade uranium-containing molybdenum ore. The low-grade uranium-containing molybdenum ore contains a high amount of mud, with extremely finely embedded molybdenum minerals. Molybdenum is present in the form of oxides within the limonite, and the grade is low, with a uranium content of 0.01-0.03% and a molybdenum content of 0.2-0.4%. Leaching the U and Mo in this ore is difficult, as it is easily silted and difficult to finely grind. This makes efficient leaching difficult at high heap heights (e.g., above 6 meters). To address the challenges faced by heap leaching of muddy, low-grade uranium-containing molybdenum ore with its unique physicochemical characteristics, the present invention, after in-depth research, provides the following solutions:
[0009] A heap leaching method for muddy low-grade uranium-containing molybdenum ore, wherein the muddy low-grade uranium-containing molybdenum ore is crushed to obtain mineral fines;
[0010] The mineral fines, concentrated sulfuric acid and water are granulated and then subjected to slaking treatment to obtain slaking material;
[0011] The slaking material is roasted at a temperature of 250-500° C., and then cooled, heaped, and acid-leached (acid heap leaching) to obtain a leachate enriched with molybdenum and uranium.
[0012] In order to solve the problems that muddy low-grade uranium-containing molybdenum ore minerals are prone to mudification, difficult to refine particles, difficult to heap leaching, and especially difficult to heap leaching in high piles, the present invention innovatively crushes the minerals and further combines the sulfuric acid aging and roasting processes. This can optimize the physical and chemical structure of the minerals, solve the problems of mudification and interstitial intercalation and symbiosis, improve the leaching performance and effect of the characteristic minerals, and especially significantly improve the heap leaching effect under high piles.
[0013] In the present invention, the mud content of the argillaceous, low-grade uranium-containing molybdenum ore is 5-10% by weight of the ore. The molybdenum minerals are extremely finely embedded, with particle sizes less than 5 μm. 40-70% of the molybdenum is present in the limonite in an isomorphous form, with uranium content ranging from 0.01-0.03% and molybdenum content ranging from 0.2-0.4%. Research conducted by the present invention has shown that it is difficult to improve the leaching rate of such minerals by particle refinement, especially by achieving high-heap leaching. However, the treatment of the present invention optimizes the physicochemical structure, achieving excellent leaching under high-heap conditions without the need for significantly refined particle precursors. This process achieves excellent leaching results while also offering excellent heap leaching costs.
[0014] The solution of the present invention does not require fine grinding of the minerals, and thus, in conjunction with the subsequent aging-roasting process, can simultaneously solve the problems of mineral muddiness and difficulty in high-heap leaching.
[0015] In the present invention, the crushing means can be conventional.
[0016] As a preferred solution, in the present invention, the crushing process includes coarse crushing, medium crushing and fine crushing processes.
[0017] In the present invention, the coarse crushing process is carried out in a jaw crusher.
[0018] In the present invention, the secondary crushing process is carried out in a cone crusher.
[0019] In the present invention, the fine crushing process is carried out in a high pressure roller mill.
[0020] In the present invention, the granulation process is carried out in a drum granulator.
[0021] In the present invention, the particle size of the mineral fine material is below 2 mm, and the proportion of particles below -1 mm is above 60%.
[0022] In the present invention, the concentration of the concentrated sulfuric acid is above 92%.
[0023] In the present invention, the amount of concentrated sulfuric acid added is 10-15% of the mass of the mineral fine material, and can further be 12-14%. The amount of water added is 6-10% of the mass of the mineral fine material, and can further be 7-8%.
[0024] Preferably, the residence time in the granulator is 3 to 5 minutes.
[0025] In the present invention, the temperature in the aging stage is 50 to 60°C.
[0026] Preferably, the temperature during the maturation stage is the heat released by the body.
[0027] Preferably, the aging time is 3 to 6 hours.
[0028] In the present invention, the roasting stage is carried out in a rotary kiln.
[0029] In the present invention, on the basis of the above-mentioned maturation, the low-temperature roasting treatment is further combined to optimize the physical and chemical structure of the mineral, for example, to improve the dissociation and physical characteristics of the mineral, thereby solving the problem that the finely embedded minerals that are easy to muddy are easy to muddy and difficult to be leached in high piles.
[0030] Furthermore, the calcination temperature is 250-400°C.
[0031] In the present invention, the calcination time is 10 to 40 minutes, and can be further extended to 15 to 30 minutes in consideration of the processing efficiency.
[0032] In the present invention, the cooling method after roasting is water cooling by spraying a dilute sulfuric acid solution. In the present invention, the sulfuric acid water cooling can be combined with the aging-roasting process to further solve the problem that the characteristic mineral is easy to mud and difficult to leaching in high piles.
[0033] In the present invention, the spraying amount of the dilute sulfuric acid solution is 7-10% of the mass of the product after roasting, and the dilute acid concentration is 3-5 g / L; preferably, the temperature after cooling is 20-30°C.
[0034] The technical solution of the present invention can solve the problem of difficult-to-leach high heaps for these minerals. Compared with the 2-3m heaps of conventional treatment methods, the heap height can reach 6-10m (for example, 6m, 7m, 8m, 9m, 10m), which is more than three times the height of existing uranium production heaps. This also allows for efficient leaching of minerals that are prone to mud formation and are highly embedded.
[0035] In the present invention, the acid leaching treatment can be carried out based on conventional means, for example, a sulfuric acid solution can be sprayed onto the ore pile after the pile is built to carry out the acid leaching treatment;
[0036] Preferably, the concentration of the sulfuric acid solution is 3 to 5 g / L sulfuric acid solution;
[0037] Preferably, the spray intensity is 200 to 500 L / (m 2 h), continuous spraying.
[0038] In the present invention, spraying is stopped when the molybdenum concentration in the leaching solution is lower than 20 mg / L, and the heap is washed with clean water, with a liquid-to-solid ratio of 0.1 to 0.2.
[0039] Compared with the prior art, the present invention has the following beneficial technical effects:
[0040] (1) Acid aging and roasting pretreatment are the key to improving the molybdenum leaching rate. The combination of the two not only changes the ore particle structure and porosity, but also increases the diffusion rate and chemical reaction rate of the reaction between the leaching agent and the molybdenum compound.
[0041] (2) Rapid cooling of the roasted material using acid solution helps to further optimize the physicochemical structure of the material and further improve the leaching effect of the characteristic mineral at high pile heights. For example, in the present invention, the pile height can reach 6 to 10 meters, and the ore pile still has good permeability under high flow rate spraying. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a schematic diagram of the process of mineral crushing of the present invention.
[0043] Figure 2 The figure is a schematic diagram of the process of heap leaching of minerals according to the present invention. DETAILED DESCRIPTION
[0044] The heap leaching method for muddy low-grade uranium-containing molybdenum ore includes the following steps:
[0045] (1) crushing the low-grade uranium-containing molybdenum ore after coarse crushing and medium crushing with a high-pressure roller mill;
[0046] (2) adding concentrated sulfuric acid and water to the finely crushed ore obtained in step (1) and mixing them uniformly, and sending the mixed material to a maturation silo for maturation;
[0047] (3) calcining the material after aging in step (2) at high temperature, and cooling the calcined material;
[0048] (4) piling the cooled calcined material from step (3);
[0049] (5) The ore heaped in step (4) is sprayed and leached with a low-acid solution, and the heap is washed with clean water after the leaching is completed.
[0050] The step (1) is specifically as follows: the raw ore is crushed by a three-stage two-closed-circuit crushing system consisting of a grizzly feeder, a jaw crusher, a cone crusher, a high-pressure roller mill, a vibrating screen, and a belt conveyor unit. In order to prevent the material from clogging the screen and improve the screening efficiency of fine-grained ore, both vibrating screens of the two-stage screening system use a relaxation screen, and the screen material is made of high-elasticity polyurethane. In order to prevent sticky materials such as fine mud from adhering to the inner wall of the feeder and cone crusher, a grizzly feeder is used. The undersize material of the grizzly feeder is combined with the discharge of the jaw crusher and then enters the first-stage screening system for pre-screening. The first-stage relaxation screen consists of two layers of screens, the upper screen has an aperture of 30 mm, and the lower screen has an aperture of 2 mm. The undersize material is combined with the undersize material of the second stage and sent to the fine crushing bin. The material on the first screen enters a cone crusher. This material is then combined with the finely crushed material from the high-pressure roller mill before entering a second screening system. The second-stage relaxation screen has an upper mesh size of 12mm and a lower mesh size of 2mm. After fine crushing, the ore has a particle size no larger than 2mm, with at least 60% of the ore below -1mm.
[0051] In step (2), the finely crushed ore is uniformly mixed with concentrated sulfuric acid and water. The equipment used is a cylindrical granulator. The amount of concentrated sulfuric acid added is 10-15% of the ore mass, and can be further 12-14%. The amount of water added is 6-10% of the ore mass, and can be further 7-8%. The material resides in the cylindrical granulator for 3-5 minutes. The concentration of concentrated sulfuric acid used is greater than 92%. To prevent the material from adhering to the inner wall of the granulator, the inner wall of the granulator is lined with a high-density anti-corrosion rubber soft board. The uniformly mixed material is sent to the maturation bin for maturation. The maturation process does not require additional heating of the material. Instead, the heat generated by the dilution of sulfuric acid and the reaction with the ore is fully utilized to mature the material. The temperature is 50-60°C, and the material resides in the maturation bin for 3-6 hours. The number of maturation bins is configured according to production conditions. Each maturation bin has a storage capacity of 500-1000 tons. The maturation bin is a fully enclosed structure with an exhaust gas collection system installed on the top and a material anti-clogging device installed on the bottom.
[0052] In step (3), the slaking material is sent to a rotary kiln for roasting. The roasting fuel is coal gas or natural gas. The fuel is directly injected and burned in the furnace. During the roasting process, the temperature of the rotary kiln feed end is controlled at 150-200°C, the temperature inside the kiln is 250-500°C, and the temperature at the outlet end is 220-300°C. The material is roasted in the rotary kiln for 10-40 minutes. Considering the processing efficiency, it can be further extended to 15-30 minutes. The waste gas generated during the roasting process is sent to the waste gas treatment system for sulfuric acid recovery and waste gas treatment. The high-temperature material after roasting is directly sent to a rotary drum cooler for cooling. The cooling method is to directly spray dilute sulfuric acid solution on the high-temperature ore. The spraying amount is 7-10% of the ore mass and the dilute acid concentration is 3-5g / L to cool the ore to 20-30°C. During the ore cooling process, the high-temperature material comes into contact with water. Due to the temperature difference, further cracks are generated inside the ore, increasing the mineral reaction area. At the same time, the sulfuric acid in the water can react with the target minerals in the ore, which is beneficial to the dissolution of the target minerals. The waste gas generated during the cooling process is sent to the waste gas treatment system to recover the sulfuric acid.
[0053] In the step (4), the cooled material is piled. Since the ore is treated with acid and high-temperature roasting, the physical properties of the ore itself are changed, and it is not easy to become muddy during the heap leaching process. Compared with the conventional treatment method of heaping 2 to 3 meters, the heap height can reach 6 to 10 meters, and the permeability of the ore heap is greatly improved. A sulfuric acid solution with a concentration of 3 to 5 g / L is used for spraying. Under continuous spraying, the permeability of the ore heap can always be maintained at 200 to 500 L / (m 2 h), which cannot be achieved by conventional heap leaching methods.
[0054] In the step (5), spraying is stopped when the molybdenum concentration in the leaching solution is lower than 20 mg / L, and the pile is then washed with clean water, with a liquid-to-solid ratio of 0.1 to 0.2.
[0055] Example 1
[0056] The mud content of a low-grade uranium-containing molybdenum ore is 5.85% by weight of the ore, the particle size of the molybdenum mineral is less than 5 μm, 45% of the molybdenum exists in the form of isomorphous inclusions in limonite, the uranium grade is 0.02%, and the molybdenum grade is 0.28%. The processing cost of existing technologies for achieving efficient extraction of uranium and molybdenum is greater than 500 yuan per ton of raw ore. The present invention is operated according to the following steps:
[0057] (1) After coarse crushing by jaw crusher, medium crushing by cone crusher and fine crushing by high pressure roller mill, the particle size of ore is less than -2mm, of which the particle size below -1mm accounts for 65.3%.
[0058] (2) The finely crushed ore is mixed with concentrated sulfuric acid and water using a cylindrical granulator. The amount of concentrated sulfuric acid added is 13% of the mass of the ore, and the amount of water added is 8% of the mass of the ore. The concentration of concentrated sulfuric acid is 92.6%, and the material residence time is 4 minutes.
[0059] (3) The material after acidification is matured in the maturation bin for 5 hours, and the temperature is monitored at 55°C during the maturation process.
[0060] (4) The slaking material is sent to a rotary kiln for roasting at a temperature of 300°C for 20 minutes. The pre-roasted material is sent to a rotary cooler for spraying with a sulfuric acid solution having a concentration of 3g / L to cool it down. The spraying amount is 8% of the mass of the ore. The temperature of the ore after cooling is 25°C.
[0061] (5) The roasted and cooled materials are piled up to a height of 6m.
[0062] (6) Use 5g / L sulfuric acid solution for spraying, and the spray intensity is 200L / (m 2 h), continuous spraying.
[0063] (7) When the molybdenum concentration in the leaching solution is lower than 20 mg / L, stop spraying and then spray clean water to wash the pile, with a liquid-to-solid ratio of 0.2.
[0064] The uranium and molybdenum contents in the final leaching residue are 0.006% and 0.05% respectively, and the uranium and molybdenum leaching rates are 70% and 82.1% respectively. The processing cost is only 410 yuan per ton of raw ore.
[0065] In summary, for the above-mentioned difficult-to-treat minerals with high mud content, ultrafine embedding and low grade, the method of the present invention can still achieve leaching at a high pile height. Not only that, it can also obtain excellent leaching effects. The process can significantly reduce the leaching cost of such minerals.
[0066] Example 2
[0067] The content of fine mud and clay minerals in a low-grade uranium-containing molybdenum ore is 9.8wt% of the ore weight. The particle size of the molybdenum minerals is less than 5μm. 50% of the molybdenum exists in the form of isomorphous inclusions in limonite and chlorite. The uranium grade is 0.021% and the molybdenum grade is 0.27%. The processing cost of existing technologies for efficient uranium and molybdenum extraction is greater than 500 yuan per ton of raw ore. The operation is carried out according to the following steps:
[0068] (1) After coarse crushing by jaw crusher, medium crushing by cone crusher and fine crushing by high pressure roller mill, the particle size of ore is less than -2mm, of which the particle size below -1mm accounts for 68.1%.
[0069] (2) The finely crushed ore is mixed with concentrated sulfuric acid and water using a cylindrical granulator. The amount of concentrated sulfuric acid added is 13% of the mass of the ore, and the amount of water added is 7% of the mass of the ore. The concentration of concentrated sulfuric acid is 92.6%, and the material residence time is 3 minutes.
[0070] (3) The material is matured in the maturation bin for 6 hours, and the temperature is monitored at 53°C during the maturation process.
[0071] (4) The slaking material is sent to a rotary kiln for roasting at a temperature of 370°C for 15 minutes. The pre-roasted material is sent to a rotary cooler for spraying with a 5g / L sulfuric acid solution for cooling. The spraying amount is 10% of the ore mass. The ore temperature after cooling is 30°C.
[0072] (5) The roasted and cooled materials are piled up to a height of 8m.
[0073] (6) Use 5g / L sulfuric acid solution for spraying, and the spray intensity is 400L / (m 2 h), continuous spraying.
[0074] (7) When the molybdenum concentration in the leaching solution is lower than 20 mg / L, stop spraying and then spray clean water to wash the pile, with a liquid-to-solid ratio of 0.2.
[0075] The final uranium and molybdenum leaching rates are 70% and 88.5% respectively, and the processing cost is less than 400 yuan per ton of raw ore.
[0076] Example 3
[0077] The mud content of a low-grade uranium-containing molybdenum ore is 6.2wt% of the ore weight. The particle size of the molybdenum minerals is less than 5μm. 48% of the molybdenum exists in the form of isomorphous inclusions in limonite. The uranium grade is 0.023% and the molybdenum grade is 0.21%. The processing cost of existing technologies for efficient uranium and molybdenum extraction is greater than 500 yuan per ton of raw ore. The operation is carried out according to the following steps:
[0078] (1) After coarse crushing by jaw crusher, medium crushing by cone crusher and fine crushing by high pressure roller grinding mill, the particle size of ore is less than -2mm, of which the particle size below -1mm accounts for 66.7%.
[0079] (2) The finely crushed ore is mixed with concentrated sulfuric acid and water using a cylindrical granulator. The amount of concentrated sulfuric acid added is 12% of the mass of the ore, and the amount of water added is 7% of the mass of the ore. The concentration of concentrated sulfuric acid is 92.6%, and the material residence time is 4 minutes.
[0080] (3) The curing time in the material curing bin is 4 hours, and the temperature during the curing process is monitored at 56°C.
[0081] (4) The slaking material is sent to a rotary kiln for roasting at a temperature of 270°C for 30 minutes. The pre-roasted material is sent to a rotary cooler for spraying with a sulfuric acid solution having a concentration of 5g / L to cool it down. The spraying amount is 8% of the mass of the ore. The temperature of the ore after cooling is 20°C.
[0082] (5) The roasted and cooled materials are piled up to a height of 10m.
[0083] (6) Use 5g / L sulfuric acid solution for spraying, and the spray intensity is 350L / (m 2 h), continuous spraying.
[0084] (7) When the molybdenum concentration in the leaching solution is lower than 20 mg / L, stop spraying and then spray clean water to wash the pile, with a liquid-to-solid ratio of 0.2.
[0085] The final uranium and molybdenum leaching rates were 73.9% and 80.0% respectively, and the processing cost was only RMB 395 per ton of raw ore.
[0086] Example 4
[0087] The mud content of a low-grade uranium-containing molybdenum ore is 7.8wt% of the ore weight. The particle size of the molybdenum minerals is less than 5μm. 53% of the molybdenum exists in the form of isomorphous inclusions in limonite. The uranium grade is 0.021% and the molybdenum grade is 0.33%. The processing cost of existing technologies for efficient uranium and molybdenum extraction is greater than 500 yuan per ton of raw ore. The operation is carried out according to the following steps:
[0088] (1) After coarse crushing by jaw crusher, medium crushing by cone crusher and fine crushing by high pressure roller mill, the particle size of ore is less than -2mm, of which the particle size below -1mm accounts for 67.2%.
[0089] (2) The finely crushed ore is mixed with concentrated sulfuric acid and water using a cylindrical granulator. The amount of concentrated sulfuric acid added is 13% of the mass of the ore, and the amount of water added is 8% of the mass of the ore. The concentration of concentrated sulfuric acid is 92.6%, and the residence time is 5 minutes.
[0090] (3) The curing time in the material curing bin is 5 hours, and the temperature during the curing process is monitored at 55°C.
[0091] (4) The slaking material is sent to a rotary kiln for roasting at a temperature of 320°C and a roasting time of 25 min. The pre-roasted material is sent to a rotary cooler for spraying with a sulfuric acid solution having a concentration of 5 g / L to cool it down. The spraying amount is 10% of the ore mass. The ore temperature after cooling is 27°C.
[0092] (5) The roasted and cooled materials are piled up to a height of 7.1 m.
[0093] (6) Use 5g / L sulfuric acid solution for spraying, and the spray intensity is 250L / (m 2 h), continuous spraying.
[0094] (7) When the molybdenum concentration in the leaching solution is lower than 20 mg / L, stop spraying and then spray clean water to wash the pile, with a liquid-to-solid ratio of 0.2.
[0095] The final uranium and molybdenum leaching rates were 71.4% and 81.5% respectively, and the processing cost was 420 yuan per ton of raw ore.
[0096] As can be seen from the examples, the leaching rates of uranium and molybdenum can be significantly improved by mixing low-grade uranium-containing molybdenum ore with acid, then subjecting it to aging treatment and then roasting treatment.
[0097] Example 5
[0098] Compared with Example 4, the only difference is that after calcination in step 4, the furnace is cooled (air-cooled), and other operations and parameters are the same as those in Example 4.
[0099] The results showed that the uranium and molybdenum leaching rates were 69.5% and 79.8% respectively.
[0100] Comparative Example 1
[0101] Compared with Example 4, the only difference is that the aging step (3) is not performed, and the processing of Step 4 is directly performed after Step 2 is completed. The other operations and parameters are the same as those in Example 1.
[0102] The results showed that the leaching rates of uranium and molybdenum were 60.0% and 53.57% respectively, indicating that the leaching rate decreased significantly at high pile heights.
[0103] Comparative Example 2
[0104] Compared with Example 4, the only difference is that the processing of step 4 is not performed, and the processing of step 5 is directly performed after the processing of step 3. Other operations and parameters are the same as those of Example 1.
[0105] The results showed that the ore pile was severely muddied and had poor permeability. The uranium and molybdenum leaching rates were 45.0% and 35.7% respectively.
[0106] Comparative Example 3
[0107] Compared with Example 4, the only difference is that in step 4, the temperature is controlled at 200° C., and other operations and parameters are the same as in Example 1.
[0108] The results were: the leaching rates of tantalum and molybdenum were 65.0% and 65.3% respectively.
[0109] Comparative Example 4
[0110] Compared with Example 4, the only difference is that the material in step 1 is first subjected to the roasting treatment in step 4, then subjected to the aging treatment in steps 2 and 3, and then subjected to the heap leaching treatment in steps 5 to 7. Other operations and parameters are the same as those in Example 1.
[0111] The results showed that the uranium and molybdenum leaching rates were 67.5% and 67.14% respectively.
Claims
1. A heap leaching method for muddy low-grade uranium-containing molybdenum ore, characterized in that: The low-grade uranium-containing molybdenum ore is crushed to obtain fine mineral material; The mineral fine material, concentrated sulfuric acid and water are granulated and then subjected to aging treatment to obtain aging material; The slaked material is roasted at a temperature of 250-500°C, and then cooled, piled and acid-leached to obtain a leaching solution enriched with molybdenum and uranium.
2. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The mud content in muddy low-grade uranium-containing molybdenum ore is 5-10wt% of the ore weight, the particle size of molybdenum mineral is less than 5μm, 40-70% of molybdenum exists in limonite in the form of isomorphism, its uranium content is 0.01-0.03%, and the molybdenum content is 0.2-0.4%.
3. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The crushing process includes coarse crushing, medium crushing and fine crushing; Preferably, the coarse crushing process is carried out in a jaw crusher; Preferably, the secondary crushing process is carried out in a cone crusher; Preferably, the fine crushing process is carried out in a high pressure roller mill; Preferably, the particle size of the mineral fine material is below 2 mm, and particles below -1 mm account for more than 60%.
4. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The granulation process is carried out in a drum granulator; Preferably, the concentration of the concentrated sulfuric acid is above 92%; Preferably, the amount of concentrated sulfuric acid added is 10-15% of the mass of the mineral fine material, and further can be 12-14%, and the amount of water added is 6-10% of the mass of the mineral fine material, and further can be 7-8%; Preferably, the residence time in the granulator is 3 to 5 minutes.
5. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The temperature in the ripening stage is 50-60°C; Preferably, the temperature of the maturation stage is the temperature at which it is released by itself; Preferably, the aging time is 3 to 6 hours.
6. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The roasting stage is carried out in a rotary kiln; Preferably, the calcination time is 10 to 40 minutes, and further 15 to 30 minutes.
7. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The cooling method after roasting is water cooling by spraying dilute sulfuric acid solution; Preferably, the spraying amount of the dilute sulfuric acid solution is 7-10% of the mass of the product after roasting, and the dilute acid concentration is 3-5 g / L; preferably, the temperature after cooling is 20-30°C.
8. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: The pile height is 6 m or more, preferably 6 to 10 m.
9. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 1, characterized in that: Spraying sulfuric acid solution on the piled ore for acid leaching; Preferably, the concentration of the sulfuric acid solution is 3 to 5 g / L sulfuric acid solution; Preferably, the spray intensity is 200 to 500 L / (m 2 h), continuous spraying.
10. The heap leaching method for muddy low-grade uranium-containing molybdenum ore according to claim 9, characterized in that: When the molybdenum concentration in the leaching solution is lower than 20 mg / L, stop spraying and wash the pile with clean water. The liquid-to-solid ratio of the washing pile is 0.1-0.2.
Citation Information
Patent Citations
Method for recovering uranium and molybdenum from wrapped low-grade uranium-containing molybdenum ore
CN114350985A
Method for treating complex low-grade uranium-containing molybdenum ore
CN115125405A
Comprehensive extraction method of complex uranium-molybdenum ore
CN115852140A